Sistem Informasi E-Arsip Berbasis Web Pada Komisi Penyiaran Indonesia Daerah Provinsi Sumatera Selatan - Marlindawati; Vivi Sahfitri (Jurnal Ilmiah Matrik, 2025)
This study addresses the challenge of designing and developing a web-based e-archive information system at the South Sumatra Regional Indonesian Broadcasting Commission (KPID). The system is developed using PHP as the programming language and MySQL as the database management system. This research aims to improve the effectiveness and efficiency of archiving official letters and administrative documents. The system development follows the waterfall method, which consists of four stages: requirements analysis, system design, implementation, and testing. Data were collected through interviews, observations, and literature review. The results of this study indicate that the proposed web-based e-archive information system facilitates archive data management and improves retrieval efficiency through an integrated search feature, enabling faster and more accurate document searches